Organizational intelligence and knowledge analytics - McBreen, Brian; Silson, John; Bedford, Denise (Bingley, U.K. : Emerald Publishing Limited, 2022)
Over the past century, intelligence has evolved as a practice in several distinct domains. In each domain, it is a unique set of tactics grown out of day to day practices. Its practice has been limited to functional units in large, well-funded enterprises. However, in the knowledge economy, every organization must behave intelligently. The relationship between knowledge and intelligence is a logical one, but it is not one that has been highlighted in either knowledge management or intelligence analysis. Organizational Intelligence and Knowledge Analytics expands the traditional intelligence life cycle to a new framework - Design-Analyze-Automate-Accelerate - and clearly lays out the alignments between knowledge capital and intelligence strategies. Explaining what it means to build intelligence capacity across the organization, this book also includes a toolkit of references to analytical methods. This book is intended for business managers, intelligence professionals, data scientists, competitive and strategic intelligence professionals, and researchers in change management.
Section 1. Knowledge and intelligence -- Chapter 1. Intelligence in knowledge economies and organizations -- Chapter 2. Traditional intelligence work -- Chapter 3. Intelligence work for the knowledge economy -- Chapter 4. Knowledge capital as intelligence sources section 2. New intelligence capabilities -- Chapter 5. Design capability -- Chapter 6. Analysis capability -- Chapter 7. Automate & operationalize capability -- Chapter 8. Accelerate capability section 3. Sustaining the intelligent organization -- Chapter 9. Capacity building for organizational intelligence and analytics -- Chapter 10. Assessing current intelligence capacity -- Chapter 11. Crafting and sustaining an organizational intelligence strategy -- Chapter 12. Business stories of intelligent organizations.
Includes index.
Includes bibliographical references.
Keywords: Organizational learning; Knowledge management; Business & Economics -- Information Management; Knowledge management